RESEARCH OF GENERALIZED CONVERTER OF IMMITANCE ON THE BASE OF ONE-JUNCTION TRANSISTOR FROM PARAMETERS OF ITS PHYSICAL EQUIVALENT CIRCUIT - Lischunska, Liudmyla; Baraban, Mariia; Rozhkova, Yana (Scientific Works of Vinnytsia National Technical University, 2015)
In the article the mathematical model of GCI was developed on a base of OT, which takes into account dependence of its regenerate immitans from OT physical parameters, and also was researched the dependences of regenerate immitans of Win (Wout), which is conducted of physical parameters of OT and range of workings frequencies. REFERENCES 1. Ленк Дж. Электронные схемы. Практическое руководство / Ленк Дж. – М.: Мир, 1985. – 344 с. 2. Ерофеева И. А. Импульсные устройства на однопереходном транзисторе / И. А. Ерофеева – М.: Связь, 1974. – 72 с. 3. Ольсевич А. Е. Двухбазовые диоды в автоматике / А. Е.Ольсевич, В. В.Михайлов, В. И. Беличенко – М.: Энергия, 1972. – 72 с. 4. Стафаев В. И. Теоретические и экспериментальные исследования двухбазового диода / В. И. Стафаев, А. П. Штагер. – Рига: Знание, 1986. – 525 с. 5. Філинюк М. А. Аналіз і синтез інформаційних пристроїв на базі потенційно нестійких узагальнених перетворювачів імітанса / М. А. Філинюк – Вінниця: ВДТУ, 1998. – 85 с. 6. Ліщинська Л. Б. Експериментальний метод визначення параметрів одно перехідного транзистора. В кн. «Контроль і управління в складних системах» / Л. Б. Ліщинська, А. Г. Швидюк, М. А. Філинюк – КУСС, 2008. – 137 с. 7. Пат. 41314 України на корисну модель. МПК8 G 01 R 27/28. Установка для вимірювання граничної частоти одноперехідного транзистора / Ліщинська Л. Б., Шведюк А. Г., Філинюк М. А., заявник та патентовласник Вінницький нац. техн. ун-т. – №u200900490; Заявл. 23.01.2009; Опубл. 12.05.2009, Бюл. №9.